Strategi Pemasaran Affiliate Marketing dalam Meningkatkan Penjualan Produk Fashion JINISO - Friska Adelina Sembiring; Erwin Permana; Sri Widyastuti; Efriyanto Efriyanto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The intense competition in the fashion industry drives brands to seek more effective and efficient marketing strategies. One increasingly adopted approach is affiliate marketing. This study aims to analyze the effectiveness of affiliate marketing strategies in increasing fashion product sales for the JINISO brand. The research uses a descriptive qualitative method with a case study approach on the JINISO brand, supported by secondary data such as sales reports, digital promotion activities, and affiliate performance. The results indicate that affiliate marketing significantly improves JINISO’s product sales. By leveraging a wide network of affiliates—including influencers, bloggers, and digital marketers JINISO successfully reaches a broader audience through personalized and credible promotions. This strategy also demonstrates highcost efficiency, as it is performance-based, meaning commissions are only paid when a sale occurs. Additionally, the data-driven approach enables the company to evaluate campaign effectiveness regularly and adjust it based on market preferences. Affiliate marketing is a marketing strategy that leverages consumer trust in affiliates while offering flexibility in budget management. Future recommendations include expanding the affiliate network, enhancing the quality of promotional content, and innovating the affiliate program to remain attractive and competitive amidst the dynamic fashion industry landscape.